Editorial [Hot Topic: Active and Passive Aβ-Immunotherapy: Preclinical and Clinical Studies and Future Directions: Part II (Guest Editors: Michael G. Agadjanyan and David H. Cribbs)] - Cribbs, David H.; Agadjanyan, Michael G. (CNS & Neurological Disorders - Drug Targets, 2009)
Alzheimer's disease (AD) is the leading cause of dementia among older people. An estimated 10% of Americans over the age of 65 and half of those over age 85 have Alzheimer's. More than four million Americans currently suffer from the disease, and the number is projected to balloon to 10-15 million over the next several decades. Alzheimer's is now the third most expensive disease to treat in the U.S., costing society close to 100 billion annually [1]. The clinical criteria for the diagnosis of AD include insidious onset and progressive impairment of memory and other cognitive functions; however a definitive diagnosis of AD can currently be made only at autopsy by examining brain tissue for amyloid plaques and neurofibrillary tangles. The extracellular amyloid plaques and intracellular neurofibrillary tangles represent examples of proteinopathies or proteopathies, which result from aberrant accumulation of misfolded or aggregated proteins that are believed to interfere with normal functions, and thereby either directly or indirectly contribute to disease pathogenesis. In addition to AD, misfolding or aberrant aggregation of proteins are central features of other neurodegenerative diseases as well, including tauopathies, Parkinson disease, amyotrophic lateral sclerosis, prion diseases, and the polyglutamine (polygln) diseases [2, 3]. Therapeutic strategies targeted at this class of diseases have focused on three areas: 1) reducing the production of the protein/peptide; 2) blocking the assembly of aberrant forms; or 3) promoting clearance [4].